The Challenges of the Labour Law and Economic in the Future Labour Market - Mélypataki, Gábor; Lipták, Katalin (International Journal of Engineering and Management Sciences, 2020)
The aim of the study is to examine how the effects of globalization affect the global labor market, and how high-level automation and digitalization affect the expectations of labor market actors and the world of labor law. We analyze the legal framework and the economic and social utility of acquiring competences for new challenges in the industry. We will look in more detail at the future of the low-skilled labor force in a changing labor market as a function of acquiring new competencies. We believe that changes in the labor market and novel processes will also pose new challenges for employers and employees. Changes in the labor market raise the question of what kind of benefits an outgoing worker will receive until he or she acquires new competencies. Is the social welfare system in the current sense capable of supporting lifelong learning, or is it necessary to explore alternatives such as basic income? All this needs to be done in the light of the legal and economic scrutiny of the concepts of efficiency and economy. This is because acquiring competences for the new employee also brings new added value.